Interest in food and triglyceride concentrations in children and adolescents with autistic spectrum disorder - Josiane da Cunha Luçardo; Giliane Fraga Monk; Mariane da Silva Dias; Thais Martins-Silva; Mayra Pacheco Fernandes; Juliana Costa Maia; Sandra Costa Valle; Juliana dos Santos Vaz (Elsevier, 2021)
Objective: To investigate eating behavior and serum concentration of triglycerides in children and adolescents with autistic spectrum disorder. Methods: Cross-sectional study conducted in the neurodevelopment nucleus, from October 2018 to April 2019 in a neurodevelopment center in the city of Pelotas/RS. Blood samples were collected, and serum was essayed for triglycerides by colorimetric enzymatic reaction. The Children's Eating Behavior Questionnaire was applied to the parents. The comparison between two or three categories of variables was performed with nonparametric tests. Linear regression was used to access the association between the log triglyceride serum concentration and the score above or below the median score of the food response and emotional overeating subscales. Results: Sixty patients were evaluated. The average age was 8.6 ± 3.2 years and most were white (75 %), male (80 %), and overweight (66%). Half of the sample had elevated triglycerides. Triglyceride concentrations were higher among overweight children and adolescents with higher median scores on the "food response" and "emotional overeating" subscales. In the adjusted analysis, the association between triglycerides and higher scores on subscales reflecting interest in food remained significant. Conclusion: Children and adolescents with autistic spectrum disorder present high triglyceride concentrations associated with a greater interest in food. Knowledge of this eating behavior may provide more effective nutritional intervention in this population.